Obesity in haemophilia patients: effect on bleeding frequency, clotting factor concentrate usage, and haemostatic and fibrinolytic parameters. (10th May 2013) - Tuinenburg, A.; Biere‐Rafi, S.; Peters, M.; Verhamme, P.; Peerlinck, K.; Kruip, M. J. H. A.; Laros‐Van Gorkom, B. A. P.; Roest, M.; Meijers, J. C. M.; Kamphuisen, P. W.; Schutgens, R. E. G.
Summary: The prevalence of obesity in patients with haemophilia (PWH) is increasing. We investigated the effect of obesity on bleeding frequency and clotting factor concentrate (CFC) usage in PWH and assessed whether prothrombotic changes observed in obesity differ between controls and PWH. Number of bleeds and CFC usage were compared between obese ( N = 51) and non‐obese ( N = 46) haemophilia A patients. Markers of haemostasis and fibrinolysis were compared between PWH, and gender‐, age‐ and body mass index (BMI)‐matched non‐haemophilic controls ( N = 91). Median number of bleeds/patient‐month was comparable between obese and non‐obese patients with severe haemophilia ( P = 0.791). Obese patients with severe haemophilia used 1.4 times more CFC/patient‐month than non‐obese patients ( P = 0.036). When adjusting for weight this difference disappeared ( P = 0.451). von Willebrand factor plasma concentration (VWF:Ag), factor VIII activity and endogenous thrombin potential were higher in obese than in non‐obese controls. Obesity did not influence these markers in PWH. Plasminogen activator inhibitor type 1 levels were higher in obese vs. non‐obese PWH ( P < 0.001), whereas levels were comparable between PWH and controls ( P = 0.912). Plasmin‐α2‐antiplasmin complex (PAP) levels appeared to be lower in obese vs. non‐obese subjects, both within controls ( P = 0.011) and PWH ( P = 0.008). However, in PWH, PAP levels were higher than in controls ( P < 0.001). Obesity is associated with an increase in net CFC usage in PWH, but has no effect on bleeding frequency. In addition, obesity attenuates hyperfibrinolysis in PWH. Future research investigating whether obese PWH need CFC treatment dosed on weight or whether a lower dosage would suffice to prevent and treat bleedings is needed.